2009
DOI: 10.3174/ajnr.a1586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intra-Arterial Injection Parameters on Arterial, Capillary, and Venous Time-Concentration Curves in a Canine Model

Abstract: BACKGROUND AND PURPOSE:Recent advances in flat panel detector angiographic equipment have provided the opportunity to obtain physiologic and anatomic information from angiographic examinations. To exploit this possibility, one must understand the factors that affect the bolus geometry of an intra-arterial injection of contrast medium. It was our purpose to examine these factors in a canine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…Our results show a smaller peak height and larger FWHM for AIFs when the injection duration was longer than 10 s. This is in accordance with the literature, shown in a simulation study and three in vivo studies in animals . All of these studies showed a smaller peak height, in combination with peak widening, for longer injection durations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show a smaller peak height and larger FWHM for AIFs when the injection duration was longer than 10 s. This is in accordance with the literature, shown in a simulation study and three in vivo studies in animals . All of these studies showed a smaller peak height, in combination with peak widening, for longer injection durations.…”
Section: Discussionsupporting
confidence: 92%
“…The most reliable TKA estimation was achieved with high injection volumes (45 mL) . These findings are supported by animal studies . However, the influence of the injection duration on the AIF and TKA parameters has not been investigated in patient studies.…”
Section: Introductionmentioning
confidence: 75%
“…In the absence of established protocols, we had to rely on initial animal studies. 27,37 Bolus watching seems to provide the best chance to ensure that the fill run is acquired during a steady state of parenchymal opacification while still minimizing the amount of contrast medium that is used. Therefore we used 80 mL of contrast material without a saline chase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that within wide variation, the position of a catheter has very limited impact on the geometry of an arterial contrast medium bolus. 7 Image sequences that were suboptimal because of patient movement were excluded as were ones in which the series did not extend from a time when there was no arterial opacification through a late venous phase of the circulation. Six readers were selected to include 3 experienced observers and 3 observers with limited experience in cerebral angiography.…”
Section: Methodsmentioning
confidence: 99%